The relationship between pain and disruptive behaviors in nursing home resident with dementia - Ahn Hyochol; Horgas Ann (BMC Geriatrics, 2013)
Abstract Background Nursing home residents with dementia gradually lose the ability to process information so that they are less likely to express pain in typical ways. These residents may express pain through disruptive behaviors because they cannot appropriately verbalize their pain experience. The objective of this study was to investigate the effect of pain on disruptive behaviors in nursing home residents with dementia. Methods This is a secondary analysis of the Minimum Data Set (MDS 2.0) assessment data on long-term care from the state of Florida. The data used in this study were the first comprehensive assessment data from NH residents with dementia aged 65 and older (N = 56,577) in Medicare- or Medicaid-certified nursing homes between January 1, 2009 and December 31, 2009. Variables examined were pain, wandering, aggression, agitation, cognitive impairment, activities of daily living impairments, and demographic characteristics. Ordinal logistic regression was used to evaluate the effect of pain on disruptive behaviors. Results Residents with more severe pain are less likely to display wandering behaviors (OR = .77, 95% CI for OR = [0.73, 0.81]), but more likely to display aggressive and agitated behaviors (OR = 1.04, 95% CI for OR = [1.01, 1.08]; OR = 1.17, 95% CI for OR = [1.13, 1.20]). Conclusions The relationship between pain and disruptive behaviors depends on the type of behaviors. Pain is positively correlated with disruptive behaviors that do not involve locomotion (e.g., aggression and agitation), but negatively related to disruptive behaviors that are accompanied by locomotion (e.g., wandering). These findings indicate that effective pain management may help to reduce aggression and agitation, and to promote mobility in persons with dementia.